2000
DOI: 10.1126/science.287.5454.851
|View full text |Cite|
|
Sign up to set email alerts
|

Honeybee Navigation: Nature and Calibration of the "Odometer"

Abstract: There are two theories about how honeybees estimate the distance to food sources. One theory proposes that distance flown is estimated in terms of energy consumption. The other suggests that the cue is visual, and is derived from the extent to which the image of the world has moved on the eye during the trip. Here the two theories are tested by observing dances of bees that have flown through a short, narrow tunnel to collect a food reward. The results show that the honeybee's "odometer" is visually driven. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
263
2
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(281 citation statements)
references
References 11 publications
11
263
2
5
Order By: Relevance
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 . Optic flow intensity is proportional to the distance from objects only during translational movements, but not during rotational movements when it is proportional to the rotational velocity of the agent.…”
Section: Review Insightmentioning
confidence: 99%
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 . Optic flow intensity is proportional to the distance from objects only during translational movements, but not during rotational movements when it is proportional to the rotational velocity of the agent.…”
Section: Review Insightmentioning
confidence: 99%
“…Bees rely on optic flow to measure translations (Srinivasan et al, 2000), while ants gauge distance mainly through proprioceptors located on joints between the insect's main body parts (Wohlgemuth et al, 2001). Measuring the ground distance, and not the distance actually walked, desert ants are able to compensate for undulations in the terrain in order to calculate the straight-line distance back to the nest (Wohlgemuth et al, 2001).…”
Section: Distancementioning
confidence: 99%
“…Bees and ants traveling between their nest and a food source learn the vector components of their movements (direction and distance) by a dead reckoning (path integration) process (Wehner, 1992). Landmarks experienced en route may serve to calibrate measured distances (Srinivasan et al, 2000a), thus reducing the rotatory and translatory errors that may accumulate during path integration (Wehner et al, 1996;Graham and Collett, 2002). Furthermore landmarks may provide procedural information about turns to make and distances to travel next (Collett, 1996(Collett, , 1998Collett and Collett, 2000;Kohler and Wehner, 2005) such that apparently complex performances could be based on simple rules of learning sensory-motor connections.…”
Section: Navigationmentioning
confidence: 99%
“…The length of the single waggle-runs increases with the distance flown to reach the source, and their angles relative to gravity correlate with the direction of the foraging flights relative to the sun's azimuth in the field and sun-linked patterns of polarized skylight. Thus, by encoding the visually measured distance (Esch and Burns, 1995;Srinivasan et al, 2000a;Tautz et al, 2004) and the direction toward the goal, the waggle dance allows colony members to share information about the distance and direction toward a desirable goal (von Frisch, 1967;Seeley, 1995;Dyer, 2002). Although Karl von Frisch used the term ''dance language,' ' Premack and Premack (1983) correctly stated that the honeybee dances should not be called a language, based on the argument that there is no evidence that the bees can judge whether their dances conform to anything in their surroundings.…”
Section: Communicationmentioning
confidence: 99%